the Mission of the Iraqi E-press in crystalizing Public Orientation of Baghdad Towards Local Political Issues. - Ali, Mustafa Faris; Alsaraj, Shukria Kawkaz (ALBAHITH ALALAMI, 2021)
This dissertation explores the role of Iraqi E-press in crystallizing the orientations or directions of the public towards the local political issues like (demonstrations, parliamentarian elections, provincial elections, the public budget and its consequences, Iraq’s relations with neighboring countries, Iraqi HOR and its sessions, and the relation of the federal government with KRG). The dissertation’s main problem revolves around a central inquiry: what is the role of the Iraqi E-press in crystalizing the direction of the Iraqi public towards the local political issues? The dissertation included a number of assumptions; the first assumes the relation of demographic variants (gender, age, social status, education, working status and residence) and the degree of dependence of the research samples upon e- press as a source of information concerning local political issues. The second assumes a relation between demographic variants (gender, age, social status, education, working status and residence) and the mode of interaction of the research samples with the published e-press outlets and rate of usage. The dissertation aims to achieve several goes including recognition of Iraqi e-press favored by public audience to track the local political issues and be acquainted with journalism arts favored by Iraqi e-press audiences and also the role of this follow up in building public awareness in terms of local political issues. The dissertation also seeks to uncover to what extent the Iraqi audience depends upon Iraqi e-press to be informed about local political issues. The dissertation depends upon the survey method, in order to describe the public directions in Baghdad concerning the political issues via Iraqi e-press, since this method is concerned in the means, procedures and tools that are used in the descriptive study of local political issues. The researcher made benefit of the descriptive part of the survey method in order to reach the Baghdad audience’s directions in a given period concerning local political issues. The researcher depended the snowball sampling method to investigate the relation between e-press and audience orientation concerning local political issues where the size of the sample was 1536 persons and used the electronic survey and personal interviews as tools of research. The dissertation reached several results including: Iraqi e-press does play a role in crystalizing the public direction concerning local political issues where most of the samples investigated follow Alsabah electronic journal. The top rated items being followed were the news then the reports that deal with the local political issues if compared with the rest of journalism arts; most Iraqis depend on Iraqi e-press as a source of information about the local political issues. The researchers recommended that Iraqi e-journals, to update and modernize their sites in order to receive the audience’s participations since the audience has become the user and main contributor to the content of these sites. Also to put effort in providing interactive boxes that act as commentary spaces concerning what was published. It is also important to provide the means of sharing the published content so that the audience may send the content to other e-journals. Uses